Pacific Alliance countries: Policy framework report on vocational education and training - Ursula Renold; Katherine M. Caves; Johanna Kemper; Maria Esther Egg (ETH Zurich, KOF Swiss Economic Institute, 2017)
Switzerland and Germany would like to establish close relationships in the field of Vocational Education and Training (VET) in the four countries of the Pacific Alliance (PAC): Mexico, Chile, Columbia and Peru. The present report provides a brief analysis of the education systems of the four countries as well as a short analysis of the challenges and opportunities regarding the improvement of VET in those four countries. This report starts with a short description of the current VET approaches in the four PAC, followed by an analysis of the strengths, weaknesses, opportunities and threats (SWOT) in each country's governance, training approach and workplace-training, permeability, youth labour market outcomes, and equity with regard to benchmark countries such as Germany and Switzerland. Subsequently, the report emphasizes the importance of capacity building and outlines possible ways of contribution by multinational companies such as Nestlé in order to strengthen the linkages between actors from the education and employment system.
Keywords: 330